Unraveling dynamic transcriptomic changes in sheep's lactating mammary gland following Escherichia coli lipopolysaccharide exposure - R. Pelayo; B. Gutiérrez-Gil; H. Marina; P.A.S. Fonseca; M. Alonso-García; J.J. Arranz; A. Suárez-Vega (Journal of Dairy Science)
ABSTRACT: Mammary gland infections constitute a significant challenge in dairy sheep, affecting productivity and welfare. Temporal RNA sequencing (RNA-Seq) provide a valuable approach to evaluate the evolution of the host defensive molecular mechanisms triggered by mastitis caused by external agents or events. This study aimed to characterize the transcriptomic response of sheep mammary glands to an intramammary inflammation induced with an Escherichia coli LPS inoculation based on RNA-Seq samples generated from milk somatic cells collected at 3 time points: pre-inoculation (0 h), and 6 h and 24 h post-LPS inoculation. The differential expression analyses between the analyzed time points were performed using 2 statistical approaches: one parametric (DESeq2) and one nonparametric (Wilcoxon rank-sum test). The differentially expressed genes (DEG) commonly identified by both approaches encompass 5,872 for the 0 h versus 6 h comparison, 4,063 for the 0 h versus 24 h comparison, and 1,034 for the 6 h versus 24 h comparison. At both 6 and 24 h, transcriptomic data highlighted a significant decrease in the expression of genes linked to metabolic processes crucial for milk protein and lipid synthesis within the mammary gland. Concurrently, increased expression of genes related to the neutrophil attraction was observed for 6 and 24 h, with differences in gene expression between DEG with the highest expression at 6 h, related to T cell activation, type I interferon-mediated signaling pathway, and 24 h, related to cell-cell neutrophil adhesion extravasation or epithelial cell proliferation. In summary, this study reveals how the sheep mammary gland transcriptome responds dynamically to an LPS inoculation, providing a comprehensive understanding of how gene expression patterns evolve over time and shedding light on the molecular mechanisms driving the initial defensive response of the mammary gland against potential inflammatory challenges.